(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article will focus on the formation of a free press in Kyrgyzstan. In this process, the authors examine the basic historical and theoretical principles of free press and focus on some problems of journalistic practice. A historical and political analysis of the positive and negative effects of the market economy on the independent press will be conducted. There are cases of constant pressure from the authorities on the free press. It is also noted with regret that journalists sometimes exaggerate the whip of a particular government and become supporters and praisers of some big official who categorically does not comply with journalistic ethics and principles of a journalist.